An Argument for Regenerative Shaming Through Its use in Holocaust and American Lynching Memorials - Leach, Lindsay (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
There is a global memorial culture around the memorialization of victims of mass tragedies, but these people are dead, so then what is the goal of these radically expensive monuments? This research explores the means by in which periods of national shame are memorialized. It seeks to determine whether memory culture is important, and whether memorials to shameful or perhaps controversial collective memory are indeed beneficial. This is addressed by means of two case studies, analyzing the Memorial to the Murdered Jews of Europe in Berlin, and The National Memorial for Peace and Justice in Alabama. These 2 monuments were chosen for their aesthetic and controversial similarities. The German monument is dedicated to the 6 million Jewish people who were exterminated by the National Socialists during the Second World War, while the American monument highlights the thousands of lynchings that occurred in the United States before and after the American Civil War. For the German monument, I conducted an interview with the monument's project manager and examined the existing literature from James E. Young, who was an advisor for the monument's location and style. For the American monument, I looked at existing literature, the monument's own published work, first-hand accounts from journalists who visited the monument, as well as current responses from social media. This work also considers the varying opinions which conflict in relation to these monuments from both sides of the political spectrum. All this research is viewed through the lens of regenerative shaming as the best practice which gives true value to any monument dedicated to a period of national shame. This is a process in which the offending party, or their descendants, recognize and publicly acknowledge their wrong doings. This recognition allows for the victims or their descendant to have their pain legitimized rather than minimized, which is the first step to the reintegration of communities. Therefore, the United States should seek to heal its ever- growing racial divide by use of regenerative shaming and look to the German memory culture as an example. Financial and educational resources must be put towards to remembering and honouring of those who were victims of the American slave trade and subsequent injustices, in order that the nation may never rewrite the horrors of slavery and racial segregation.
Keywords: Identities and Cultures of Europe